Cervical dissection diagnoses increase following endovascular treatments. Issue 3 (March 2020) - Pérez-Sánchez, Soledad; Domínguez-Mayoral, Ana; De Torres-Chacón, Reyes; Gamero-García, Miguel A; Barragán-Prieto, Ana; Escudero-Martínez, Irene; Ocete, Rafael F; Herrero-Lara, Juan; Algaba, Pilar; Moniche, Francisco; González, Alejandro; Cueto, Luis; et al.
Objectives: The detection of cervical arterial dissection (CAD) has been rising in recent years owing to advanced imaging techniques. The aim of this study was to explore whether wide implementation of endovascular treatment for ischemic stroke has an impact on the diagnosis of CAD. Methods: We included all patients with CAD diagnosed at two university hospitals in Seville, Spain from January 2015 to December 2017. We collected clinical variables and information on imaging techniques used for the diagnosis. Implementation of 24 hour/365 day mechanical thrombectomy began in Seville on 15 August 2016. We compared diagnosis rates of CAD performed before and after this date. Results: We identified 41 patients with CAD. We found 13 patients diagnosed before (1.1% of all ischemic strokes) and 28 (2.2%) after implementation of neurointerventional therapy. In 17 patients, diagnosis was made in the acute phase. Dissection was not suspected according to computed tomography angiography in 11 patients owing to small dissections (n = 2) or total occlusion (n = 9). Conclusions: CAD diagnoses have been rising in recent years, essentially owing to continuous improvement in imaging techniques. Rapid access to arteriography for thrombectomy is increasing the diagnoses of CAD, even in patients with a low suspicion of dissection.